2018
DOI: 10.1007/s10528-018-9841-1
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant DNA Methylation in Chronic Myeloid Leukemia: Cell Fate Control, Prognosis, and Therapeutic Response

Abstract: Chronic myeloid leukemia (CML) is a hematopoietic stem cell malignancy characterized by the expression of the BCR-ABL1 fusion gene with different chimeric transcripts. Despite the crucial impact of constitutively active tyrosine kinase in CML pathogenesis, aberrant DNA methylation of certain genes plays an important role in disease progression and the development of drug resistance. This article reviews recent findings relevant to the effect of DNA methylation pattern of regulatory genes on various cellular ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 133 publications
0
8
0
Order By: Relevance
“…Several studies documented about the effect of DNA methylation pattern of regulatory genes on various cellular activities such as cell proliferation and survival, as well as cell-signaling molecules in CML [43]. Jelinek et al 2011 studied the Methylation levels of 10 genes in CML patients and found that the frequency of methylated genes ranged from 11%-86% as follows: ABL1 (86%), CDH13 (79%), NPM2 (74%), PGRA (66%), TFAP2E (63%), DPYS (54%), PGRB (52%),OSCP1 (30%), PDLIM4 (21%) and CDKN2B (11%), This indicates that there is aberrant methylation of DNA associated with the progression of CML [44].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies documented about the effect of DNA methylation pattern of regulatory genes on various cellular activities such as cell proliferation and survival, as well as cell-signaling molecules in CML [43]. Jelinek et al 2011 studied the Methylation levels of 10 genes in CML patients and found that the frequency of methylated genes ranged from 11%-86% as follows: ABL1 (86%), CDH13 (79%), NPM2 (74%), PGRA (66%), TFAP2E (63%), DPYS (54%), PGRB (52%),OSCP1 (30%), PDLIM4 (21%) and CDKN2B (11%), This indicates that there is aberrant methylation of DNA associated with the progression of CML [44].…”
Section: Discussionmentioning
confidence: 99%
“…The first studies on DNA methylation in CML were performed in blast phase cells, known for their genetic instability. The first analyses on a limited number of genes [ 36 , 37 , 38 , 39 , 40 , 41 , 42 ], reviewed in [ 43 ], suggested the existence of methylation abnormalities in CML. A tendency to DNA hypermethylation was observed in BC compared with CP-CML primary cells.…”
Section: Dna Methylation Abnormalities In CMLmentioning
confidence: 99%
“…Interestingly, although gene mutations can be present already in the pre-leukemic clone, therapeutic resistance to TKI correlates more with mutations occurring during the follow-up than with their initial presence [ 62 ]. The occurrence of these chromosomal/genetic perturbations and/or BCR-ABL point mutations during the progressive phases of the disease might reflect the well-known genetic instability in CML, probably favored by DNA methylation abnormalities [ 37 , 38 , 43 , 63 ].…”
Section: Dna Methylation Abnormalities In CMLmentioning
confidence: 99%
See 2 more Smart Citations